Keragaman Jenis Kadal Sub Ordo Sauria pada Tiga Tipe Hutan di Kecamatan Sungai Ambawang - Tri Rima Setyawati, Petrus Apriyanto, Ari Hepi Yanti (Universitas Tanjungpura, 2015)
Lizards are one of the group of reptiles belong to suborder Sauria with the greatest number of members on earth. This research aims to know the species of lizards of suborder Sauria and to know the environmental condition found in primary, secondary and Tembawang forests in the district of Sungai Ambawang. The research was carried out by using cruising method. The lizards seen and found were captured by usingsnare stick, pitfall trap, glue trap and direct capture. Morphological characters analyzed to identify the lizards were snout vent length and tail length. In three types of forests in Sungai Ambawang district, a total of 68 lizards of suborder Sauria were recorded, which consisted of 48 lizards from family Scincidae, 5 lizards of Gekkonidae, 3 lizards of Lacertidae, and 12 lizards of Agamidae. The result showed that the dominance index (C) in primary forest was 0,0865, secondary forest was 0,1046 and 0,1462 in Tembawang forest. Evenness index (E) of types of lizards was relatively low, with a value of 0,2248 in primary forest, 0,2644 in secondary forest and 0,2663 in Tembawang forest. The similarity index (SJ) in the three locations was around 0,5-1 where the three locations had the similarity in the species of lizards.